'And they all look just the same'? A quantitative survey of television title sequences. (May 2014) - Bednarek, Monika
This article describes the variation in title sequences for American television series (a sequence of moving images and sound at the beginning of a television series). Using a quantitative survey of 50 contemporary fictional television series, it explores key features of the television title sequence – such as length, credits, characters, sound and style – and relates these to its functional characteristics. In so doing, the article provides a synchronic snapshot of a significant contemporary cultural product that viewers regularly engage with and enjoy. The survey not only shows the variation inherent in these cultural products, but also pinpoints areas that are worth investigating more closely and in depth.